A Qualitative Study on Role of Self-Help Group in Women Empowerment in Rural Pondicherry, India - Lopamudra Sahu; Suresh K Singh (Medsci Publications, 2012)
Bacground: Women empowerment is an essential precondition for elimination of poverty. Many International and National bodies have stressed on women empowerment giving attention to their participation in society, decision-making, education and health. In India, Micro finance and Self Help Group (SHG) intervention have brought tremendous change in the life of women at the grass root level. Currently around 1640 SHGs exist in Pondicherry and are successfully managed by women. Aim: To assess the role of Self-Help Groups in empowerment of women of rural Pondicherry. Methodology: It was a community based qualitatively study. Focus Group Discussions (FGD) were conducted among six SHG groups (one each) selected on feasibility basis. The SHG members' perception of improvement in different pre determined domains were assessed. Content analysis was done manually and the key findings were noted. Results: The key responses were 'increased participation in household decision making', 'gaining respect in family', 'increased savings', 'meeting family expenses', 'improved political knowledge', 'independence', 'confidence' etc. They said to have gained respect and trust in society and were able to plan for the future of their families. Conclusions: Self Help Groups played very important role in Women empowerment and should be promoted for economic development of the country.